Life history traits, but not phylogeny, drive compositional patterns in a butterfly metacommunity. Issue 12 (1st December 2014) - Pavoine, Sandrine; Baguette, Michel; Stevens, Virginie M.; Leibold, Mathew A.; Turlure, Camille; Bonsall, Michael B.
Abstract : Community assembly is a combination of ecological, evolutionary, and stochastic processes. Separating out the abiotic and biotic processes (such as limiting similarity or environmental filtering) from stochastic processes is central to developing a cogent approach for understanding patterns in ecological community structure and organization. Using butterfly communities in a fragmented landscape, we tested the hypothesis that local environmental filtering drives character convergences in traits of species belonging to different clades. We found that, while many traits were determined both by phylogeny and environment, trait convergence within the phylogeny was extensive and eroded the phylogenetic structure associated with habitat use. Traits associated with habitat use are shown to be only moderately phylogenetically conserved in chalk grassland butterfly assemblages, and further analysis revealed that traits associated with environmental filtering may be highly labile rather than phylogenetically conserved. In general, a significant phylogenetic signal is therefore neither sufficient to demonstrate a lack of trait convergence, nor to determine whether communities are likely to be phylogenetically structured. We conclude that explicit trait‐based approaches should be used in preference to the more indirect approach based on phylogenetic conservatism for understanding metacommunity assembly processes.